Practical Key-Recovery Attacks On Round-Reduced Ketje Jr, Xoodoo-AE And Xoodyak. (4th February 2020) - Zhou, Haibo; Li, Zheng; Dong, Xiaoyang; Jia, Keting; Meier, Willi
Abstract: A new conditional cube attack was proposed by Li et al. at ToSC 2019 for cryptanalysis of Keccak keyed modes. In this paper, we find a new property of Li et al. 's method. The conditional cube attack is modified and applied to cryptanalysis of 5-round Ketje Jr, 6-round Xoodoo -AE and Xoodyak, where Ketje Jr is among the third round CAESAR competition candidates and Xoodyak is a Round 2 submission of the ongoing NIST lightweight cryptography project. For the updated conditional cube attack, all our results are shown to be of practical time complexity with negligible memory cost, and test codes are provided. Notably, our results on Xoodyak represent the first third-party cryptanalysis for Xoodyak .